Prueba hipergeométrica aleatorizada (2011)
Randomized tests are well documented in theory, but are rarely used in practical applications. With the computers, many methods based on random number generation to build statistical analysis procedures have been developed. In this article we present in detail the hypergeometric randomized test to illustrate its usefulness in terms of approaching the size of hypotheses tests based on discrete statistics to the usual signiﬁcance levels.